2020
DOI: 10.1088/1748-605x/ab9095
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of the co-release of icariin and strontium from bioactive glass submicron spheres on the reduced osteogenic potential of rat osteoporotic bone marrow mesenchymal stem cells

Abstract: Osteoporosis is a metabolic disease that affects bone tissue and is highly associated with bone fractures. Typical osteoporosis fracture treatments, such as bisphosphonates and hormone replacement, present important challenges because of their low bioavailability on the site of action. Options to overcome this issue are systems for the local release of therapeutic agents such as bioactive glasses containing therapeutic molecules and ions. These agents are released during the dissolution process, combining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In cases of individuals who have chronic diseases associated with the need for bone repair, if necessary, it can be difficult [ 65 , 66 ]. Therefore, there is a growing demand for biomaterials that have adequate properties in relation to bone tissue and that can positively influence tissue regeneration, improving biomechanical properties and accelerating the osteogenesis process [ 31 , 32 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases of individuals who have chronic diseases associated with the need for bone repair, if necessary, it can be difficult [ 65 , 66 ]. Therefore, there is a growing demand for biomaterials that have adequate properties in relation to bone tissue and that can positively influence tissue regeneration, improving biomechanical properties and accelerating the osteogenesis process [ 31 , 32 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Kyllonen et al [ 69 ] for the release and transport of the active drug, particles of different sizes can be used; therefore, the drug is incorporated, absorbed, or associated with these particles and thus is protected from the degradation from the environment until its release. In a recent study by Mosqueira et al [ 32 ], the authors concluded that the efficiency of the loading of therapeutic agents in strontium-modified bioglass spheres, as well as the drug release rates, were mainly influenced by the pore size of the particles, thus improving the osteogenic potential of the mesenchymal cells of the bone marrow obtained from rats with osteoporosis. In this study, bioglass particles were reduced to nanometer size for surface increase, as the number of surface atoms increases dramatically as the particle size decreases [ 70 ], which contributes to drug incorporation and release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two ways to rebalance bone remodeling: (1) using a single ingredient that has the properties of both promoting osteogenesis and inhibiting osteoclasts; or (2) the one plus one strategy (a combination strategy with one component promoting osteogenesis and the other component inhibiting osteoclasts). There are three categories of single ingredients that have both properties: inorganic elements (e.g., strontium, ,,, ,,,,,, europium, and gallium), clinical drugs (e.g., PTH, cholecalciferol, simvastatin, and estradiol), and MSCs . Additionally, although estradiol is classified as an antiabsorption drug in clinical applications, its dual effects on osteoclasts and osteoblasts have been demonstrated by some researchers. , Therefore, in recent studies, it has been used as an antiosteoporotic ingredient with dual effects. , Strontium ions have both pro-osteogenic and antiosteoclastogenic effects, but the low oral bioavailability and side effects associated with dose accumulation limit its clinical application. , Calcium and strontium have similar properties because they are within the same group of elements, so the substitution of strontium for calcium can be achieved in CBNMs through a simple process.…”
Section: Cbnms For Osteoporosis Treatmentmentioning
confidence: 99%
“…There are two ways to rebalance bone remodeling: (1) using a single ingredient that has the properties of both promoting osteogenesis and inhibiting osteoclasts; or (2) the one plus one strategy (a combination strategy with one component promoting osteogenesis and the other component inhibiting osteoclasts). There are three categories of single ingredients that have both properties: inorganic elements (e.g., strontium, 95,104,106,[115][116][117][118]132,135,146,148,149,153 europium, 122 and gallium 150 ), clinical drugs (e.g., PTH, 99 cholecalciferol, 126 simvastatin, 151 and estradiol 105 ), and MSCs. 125 Additionally, although estradiol is classified as an antiabsorption drug in clinical applications, its dual effects on osteoclasts and osteoblasts have been demonstrated by some researchers.…”
Section: Antiosteoporosis Cbnms In Different Applicationmentioning
confidence: 99%